Entre a cripta e o fantasma: a transgeracionalidade em Antígona, de Sófocles - Ribeiro, Prisciane Pinto Fabricio (2023)
This thesis aims to investigate the concept of psychic transgenerationality in the character of Antigone, using as the research corpus the homonymous work by Sophocles. Based on this, the face of Antigone is presented under the light of the family miasma, manifested in the work by the tragic tension of pathos, considering that the actions of the heroine, beyond a religious and political vision, are directly linked to the bloodline and tainted bond of her ancestors. To do so, it was necessary to weave, primarily, reflections on the dynamics between myth, tragedy, and psychoanalysis, as well as to present an overview of tragedy and the tragic hero, in addition to their essential concepts of pathos and catharsis, in order to establish bases for the identification of connections between the tragic hero and metapsychology. Next, we listed the Freudian perspective on heredity and phylogenetic influences on the constitution of trauma and subjectivation of the individual, as a fundamental concept for the theory of transgenerationality developed by Abraham and Torok, and their concepts of Crypt and Phantom. Finally, we present an itinerary of the race of the Labdacids, taking the miasma as the guiding element that falls on family members and generational passages up to the figure of Antigone. Based on the theory of Abraham and Torok, the research seeks to understand the transgenerational affectations of this heroine, a recipient of the family phantom, evoked by the stories and family traumas that are transmitted from generation to generation in Antigone, by Sophocles. For a better approach and a more detailed analysis of the studied work, an operational translation of the research corpus, as well as secondary works that served as a literary framework for the investigation, are provided.